Supporting School Attendance Among Indigenous Children and Youth in Canada: A Rapid Review and Call to Action - Rogers, Maria; Aglukark, Karen (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2024)
Many community leaders in Canada have asserted the need for improved school attendance to promote educational success and well-being among Indigenous students. This paper reviews the extant literature from researchers, government agencies, school districts, and other organizations that have identified factors that improve school attendance among Indigenous students in Canada. The reviewed literature and reports indicate a need for more culturally relevant supports, as well as a more wholistic approach for Indigenous students and their families. This review also highlights the dearth of research on this topic and demonstrates the need for studies and initiatives that closely examine contributing factors at various levels (i.e., administrative, policy, community, classroom, household, individual), and that deeply engage families and communities.